(untitled) (Linguostylistic Studies, 2020)
The article elucidates the phenomenon of a self-made man as an idiom, concept, and a symbol of the American culture. The meaning of the idiom is considered from the standpoint of its denotative and connotative meaning, including the historical background for its definition. The research into the nature of the concept of a self-made man is topical in the context of the growing interest of the cognitive linguistics and linguocultural studies in the axiological component of the linguistic picture of the world. The main purpose of the linguocultural studies is to disclose the mentality of the people and their cultural features via language units, and idioms, in particular. The authors consider the concept of self-made man as a complex multilateral structure that includes not only conceptual issues, but also social, psychological, and cultural components. These components include associations, emotions, evaluation, and subconcepts of hard work, perseverance, legacy appropriate for the given culture. The scope of this research has been narrowed to the case study of Bruce Lee’s success as a vivid illustration of an archetype of a self-made man to confirm the theoretical framework of this paper. The material of the case study was the book by J. Little ‘The Warrior Within: The Philosophies of Bruce Lee’. The emphasis is laid on the component of hard work as an integral and the most fundamental aspect of the concept. The categories hard work and persistence manifested the highest frequency in verbal expressions in the discourse under study. The linguoculturological approach to the study of the issue provides clues to revealing the philosophical and cultural features of the self-made man concept. The key findings of the study offer ideas to explore the culturally specific features of the image of a self-made man at a cross-cultural level.